2011
DOI: 10.1103/physrevb.83.224519
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofHe3impurity on solidHe4studied by compo

Abstract: Frequency shifts and dissipation of a compound torsional oscillator induced by solid 4 He samples containing 3 He impurity concentrations (x3 = 0.3, 3, 6, 12 and 25 in units of 10 −6 ) have been measured at two resonant mode frequencies (f1 = 493 and f2 = 1164 Hz) at temperatures (T ) between 0.02 and 1.1 K. The fractional frequency shifts of the f1 mode were much smaller than those of the f2 mode. The observed frequency shifts continued to decrease as T was increased above 0.3 K, and the conventional non-clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Day and Beamish [5] discovered that the shear modulus of solid 4 He showed strikingly similar behaviors as those found in torsional oscillator experiments in temperature dependence, nonlinearity and hysteresis [6] in drive dependence, and dependence on 3 He impurity [7][8][9]. These similarities pointed to the shear modulus of solid 4 He contributing, at least in part, to the observed decoupling effects in TO experiments.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Day and Beamish [5] discovered that the shear modulus of solid 4 He showed strikingly similar behaviors as those found in torsional oscillator experiments in temperature dependence, nonlinearity and hysteresis [6] in drive dependence, and dependence on 3 He impurity [7][8][9]. These similarities pointed to the shear modulus of solid 4 He contributing, at least in part, to the observed decoupling effects in TO experiments.…”
Section: Introductionmentioning
confidence: 54%
“…The sample container attached to the TO is a thin annulus (10.0 mm outer diameter, 9.6 inner diameter, 8.0 mm height). The cell design is essentially identical to that described in detail by Gumann et al [9] except for the thickness of the annular sample chamber. The sample chamber is filled through a hole (0.8 mm diameter) drilled into the BeCu torsion rod (2.0 mm diameter) of the TO.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…This is because the NCRIFs could be the signature of a supersolid state as outlined by Leggett 4 and predicted by Andreev and Lifshitz several years ago. 5 A large number of independent experiments [6][7][8][9][10] have shown that the NCRIF magnitude and temperature dependence are strongly dependent on defects such as 3 He impurities 11,12 and the quality of the crystals, and can be made very small by very careful annealing. 3 The observation of…”
Section: Introductionmentioning
confidence: 99%
“…The NCRI has now been widely reproduced in other laboratories in a variety of sample cells. [3][4][5][6][7][8][9] However, the magnitude of the NCRI observed varies between zero and 1.5 %, depending on how the sample is prepared, quenched or annealed, on the 3 He concentration and on other factors. This suggests that the NCRI is associated with defects in the solid, dislocations, grain boundaries, amorphous regions or other defects.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the NCRI is associated with defects in the solid, dislocations, grain boundaries, amorphous regions or other defects. [10][11][12][13] The magnitude and character of the NCRI depends on the oscillator frequency 7,8,14 and shows effects 15,16 not usually associated with superflow. For example, the NCRI is associated with substantial elastic energy dissipation in the solid described by the Q of the oscillator.…”
Section: Introductionmentioning
confidence: 99%